Association between oral health status and frailty in older adults: a systematic review and meta-analysis - Huang, Jingwen; Zhang, Yin; Xv, Min; Sun, Likai; Wang, Mei (Frontiers in Public Health, 2025)
AimThis study aims to explore the association between oral health status and frailty in older adults using comprehensive and objective oral health measurement indicators.MethodThis study conducted a collection and retrieval of relevant literature in the following English databases: PubMed, Embase, Cochrane Library, and Web of Science (up to July 1, 2024). After screening the literature according to the specified inclusion and exclusion criteria, the quality of the literature was assessed using the Joanna Briggs Institute critical appraisal tool and the Newcastle-Ottawa Scale. The degree of heterogeneity was then represented by the I2 statistic, and based on this result, a random-effects or fixed-effects model was determined for analysis. Odds ratios (OR)/standardized mean differences (SMD) and 95% confidence intervals were employed to identify the association between various oral health indicators and frailty. Sensitivity analysis was performed for all outcomes.ResultsA total of 28 articles were included. Number of teeth (SMD: −0.591), functional dentition (≥21 teeth) (OR: 0.236), no false teeth (OR: 0.733), ≤20 teeth/with denture (OR: 2.320), tooth brushing daily (OR: 0.562), tongue pressure/decreased tongue pressure (SMD: −0.582/OR: 1.618), occlusal force/occlusal force reduced (SMD: −0.526/OR: 1.846), oral diadochokinesis hypofunction (OR: 1.876), poor mixing ability (OR: 2.303) and oral health assessment tool scores ≥4 (OR: 2.501) were correlated with frailty in older adults.ConclusionVarious types of oral health indicators are associated with frailty in older adults. Investigating the relationship between oral health and frailty in older adults is of significant importance for preventing frailty, ensuring the quality of life for older adults, and promoting healthy longevity.Systematic review registrationPROSPERO CRD42024587687.